2017
DOI: 10.9734/jabb/2017/33701
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Molecular Analysis of Wild Edible Gelam Mushroom (Boletus sp.) from Kelantan, Malaysia

Abstract: Aims: To conduct nutritional and molecular analysis of Gelam mushroom which is believed to have contained medicinal properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Fresh TBB samples contained a moisture content of 82.7 ± 2.0% on a wet-weight basis. Our results agreed with the findings of previous studies that found that the moisture content in fresh bolete mushrooms ranged from 70% to 93% depending upon the bolete species [ 43 , 44 , 45 , 46 , 47 ]. To extend the availability and shelf-life of TBB, a preservation method is recommended.…”
Section: Resultssupporting
confidence: 93%
“…Fresh TBB samples contained a moisture content of 82.7 ± 2.0% on a wet-weight basis. Our results agreed with the findings of previous studies that found that the moisture content in fresh bolete mushrooms ranged from 70% to 93% depending upon the bolete species [ 43 , 44 , 45 , 46 , 47 ]. To extend the availability and shelf-life of TBB, a preservation method is recommended.…”
Section: Resultssupporting
confidence: 93%